Análise de estabilidade de barragens de pequeno porte – estudo de caso no semiárido nordestino - Nascimento, Francisco Jhefison do (Universidade Federal Rural do Semi-Árido, 2019)
Checking the criteria that guarantee the safety of an earth dam comes almost solely on the study of slope stability and also the severity of pathological conditions that exist on site. Based on the information obtained from studies in this in this area, an action plan can be determined that can correct the problems. found, or those that may arise. This work has the purpose of the safety study of the morada nova dam, located in the interior of Patu-RN. Its geometry was calculated based on field measurement models, and software analyzes were also performed with this data in addition to information obtained from samples collected for laboratory testing. The analyzes had to be performed because during the bibliographic survey about the dam no data were found. Slope stability studies were carried out, taking into account the state in which the dam was found, and through the simulations it was verified that one of the studied points presented a slope considered above the recommended, which may cause problems regarding its safety. Therefore, according to the information obtained, it was possible to understand a specific point that needs a correction measure, even considering that the location has no indication of problems, which arouses the need to further study where they were detected. failures, in order to prevent any problems that may arise and also to guide the government agencies in case of any dam expansion project.
Monografia
Keywords: Barragem de terra; Estabilidade de taludes; Inclinação; Semi árido; Earth dam; Slope stability; Slope; Semi arid; ENGENHARIAS::ENGENHARIA CIVIL